ISLAM DI INDONESIA SEBELUM KEMERDEKAAN - Duriana Duriana (IAIN Ambon, 2018)
This paper discusses Islam in Indonesia before independence which includes the development of Islam before the Dutch colonial period, the Dutch colonial period and during the Japanese occupation. Based on the research literature by using critical analytical methods, found the idea that the development of Islam in Indonesia before the Dutch colonial period through three phases, namely the presence of Muslim traders phase, the phase of the formation of the Islamic empire (1316 AD) and Islam institutionalization phase. The development of Islam in the Dutch colonial period and the occupation of Japan experienced a period of decline tidal namely Islam, a period of national awakening, and the critical period of Islam. During the Japanese occupation, the role of Islam in politics in the country weakened. It was as a result of the challenges of secular nationalism and the suppression of the Netherlands and Japan on suspicion of Muslim political loyalty